(untitled) (Eurasian Scientific Herald, 2023)
With the onset of the global pandemic, the role of digital technology has grown significantly, demonstrating the importance of digital transformation, especially for developing countries, including Uzbekistan . Indeed, digital transformation has the potential to further modernize society and improve the competitiveness of the national economy. From this point of view, there is a special emphasis on implementingn reforms, as well as digitizing all key areas within the framework of new Uzbekistan’s Development Strategy for the next five years and establishing a real information society in the country.